PARS PLANA VITRECTOMY FOR THE TREATMENT OF TRACTIONAL AND DEGENERATIVE LAMELLAR MACULAR HOLES: Functional and Anatomical Results. Issue 11 (November 2019) - Figueroa, Marta S.; Govetto, Andrea; Steel, David H.; Sebag, J.; Virgili, Gianni; Hubschman, Jean Pierre
Abstract : Purpose: Functional and anatomical outcomes of vitrectomy with membrane peeling were compared in tractional lamellar macular holes (LMH)/macular pseudoholes (MPH) versus degenerative LMH. Methods: This multicenter retrospective study enrolled patients with a minimum follow-up of 6 months. The association of spectral domain optical coherence tomography parameters with preoperative and postoperative best-corrected visual acuity was analyzed. Results: Seventy-seven (74.8%) tractional LMH/MPH and 26 (25.2%) degenerative LMH were included. Preoperative best-corrected visual acuity was better in tractional LMH/MPH (0.39 ± 0.2 logarithm of the minimal angle of resolution, 20/50 Snellen equivalent) than degenerative LMH (0.56 ± 0.2 logarithm of the minimal angle of resolution, 20/66 Snellen equivalent; P < 0.001). Premacular membranes were found in all tractional LMH/MPH, whereas LMH-associated epiretinal proliferation (LHEP) was present in all degenerative LMH. Primary anatomical success was achieved in 97/103 eyes (94.2%), with foveal restoration occurring earlier in degenerative LMH (1.6 ± 2.3 vs. 3.3 ± 3.6 months; P = 0.025). Best-corrected visual acuity improved in both tractional LMH/MPH and degenerative LMH ( P < 0.001 and P = 0.012, respectively) but was better in tractional LMH/MPH ( P = 0.001). Conclusion: The presence of premacular membranes and absence of LMH-associated epiretinal proliferation in all tractional LMH/MPH further distinguishes this from degenerative LMH. Best-corrected visual acuity improved in both subgroups but more so in tractional LMH/MPH. Complete anatomical restoration of foveal microanatomy was rare in degenerative LMH, reflecting significant morphological and pathophysiological differences between the two lesions. Abstract : Pars plana vitrectomy with membrane peeling in the treatment of tractional lamellar macular holes (LMH)/macular pseudoholes and degenerative LMH has greater functional improvement in the tractional LMH/macular pseudohole subgroup. Complete postoperative anatomical restoration occurred in the majority of tractional LMH/macular pseudohole lesions, but not in degenerative LMH.